Morphological Distribution of the Anterior Inferior Iliac Spine in Patients With and Without Hip Impingement: Reliability, Validity, and Relationship to the Intraoperative Assessment. (April 2017) - Balazs, George C.; Williams, Benjamin C.; Knaus, Christopher M.; Brooks, Daniel I.; Dickens, Jonathan F.; McCabe, Michael P.; Anderson, Terrence D.
Background: Subspinous impingement of the anterior inferior iliac spine (AIIS) on the femoral head-neck junction is increasingly recognized as a source of hip impingement. A classification system of AIIS morphology has previously been proposed that correlates with reduced hip motion and may predispose patients to subspinous hip impingement. Purpose: To examine the morphological distribution of AIIS types in patients with and without diagnosed hip impingement and correlate AIIS morphology to intraoperative findings at the time of surgery. Study Design: Cross-sectional study; Level of evidence, 3. Methods: Three-dimensional reconstructed pelvic computed tomography scans were generated for a stratified sample of 449 hips in patients without a history of hip pain or hip impingement and 59 hips in patients with a diagnosis of hip impingement. Three blinded assessors classified the AIIS for each hip twice. The morphological distribution between symptomatic and asymptomatic patients was compared, controlling for age, sex, and affected side. Within the symptomatic cohort, AIIS morphology was compared with the intraoperative assessment of a low-lying AIIS using the Fisher exact test. Results: The intraobserver reliability of the classification system in our cohort was substantial (κ = 0.68-0.77). The interobserver reliability was moderate (κ = 0.50). The morphological distribution between symptomatic and asymptomatic patients was similar, with 75% of patients in the asymptomatic group and 80% of the patients in the symptomatic group having a type 2 or type 3 AIIS. When matched for age, sex, and affected side, there was no significant difference in the assessed classification type between the groups ( P = .55). Within the symptomatic group, there was no significant correlation between the surgeon assessment of a low-lying AIIS and a type 2 or type 3 radiographic classification ( P = .10). The positive predictive value of a type 2 or type 3 AIIS classification for hip impingement symptoms was 10%, and the negative predictive value was 91%. Conclusion: These findings suggest that a high percentage of patients with AIIS morphology associated with subspinous impingement are, in fact, asymptomatic. The current radiographic classification scheme should not be used exclusively for clinical decision making.